Farm input subsidies and commodity market trends in Ghana: An analysis of market prices during 2012–2020 - Amewu, Sena; Arhin, Eunice; Pauw, Karl (International Food Policy Research Institute, 2021)
Ghana has a long history of intervening in food markets to balance consumers’ expectations of low and stable food prices, farmers’ demands for high farmgate prices, and traders’ demand for predictability in seasonal price patterns. However, government interventions may also alter the behavior of markets and alter incentives or risks for all market actors. The Planting for Food and Jobs (PFJ) initiative, launched in 2017, signaled a renewed commitment from government to agriculture and is Ghana’s flagship strategy for boosting smallholder production, strengthening market linkages, and developing value chains. Given this significant shift, we examine agricultural commodity price patterns before and after 2017 to identify potential structural shifts in price behavior in maize, tomato, and onion markets, three key sectors targeted by PFJ. Results show maize and tomato prices drop below their long-term trend under PFJ, but not onion prices. Tomato and onion prices exhibit smaller seasonal price variations. These results are indicative of a structural shift in food markets, although further analysis is required to conclusively attribute these changes to PFJ.